Corpus callosum microstructural and macrostructural abnormalities in schizophrenia according to the stage of disease. (30th September 2019) - Madigand, Jérémy; Tréhout, Maxime; Delcroix, Nicolas; Dollfus, Sonia; Leroux, Elise
Highlights: Illness duration (ID) remains unconsidered in callosal studies in schizophrenia. Callosal microstructural alterations were found in the short and long ID groups. Callosal macrostructural alterations were only found in the long ID group. Microstructural alterations might be an early marker of schizophrenia. Macrostructural changes might be a longer-term more severe marker of schizophrenia. Abstract: Corpus callosum (CC) volume and surface (macrostructural) studies remain controversial and have not considered the illness duration (ID) systematically. Regardless of ID, some CC macrostructural studies have shown no difference between SZ patients and healthy controls (HC), whereas others have reported macrostructural abnormalities in SZ. Conversely, CC microstructural studies are more in agreement with alterations in CC integrity regardless of the patients' ID, but the direction and degree of these abnormalities over time remain unknown. Moreover, no study has explored both the micro- and macrostructure of the CC in SZ by considering the stage of disease. Both CC micro- and macrostructural data were investigated in 43 SZ patients and compared between two patient groups (21 patients with a short ID and 22 with a long ID) and HC (23 participants) using diffusion tensor and structural imaging. CC microstructural alterations were detected in both SZ groups compared to the HC group, without differences between the SZ groups. In contrast, CC macrostructural alterations were only found in the long ID group. CC microstructural alterations might be detected in schizophrenia at an early stage, without an increase of magnitude thereafter, while CC macrostructural alterations might become apparent at later stages of the illness.